EVALUASI PANDUAN PENYUSUNAN PROGRAM AUDIT ATAS PERUSAHAAN PENERIMA FASILITAS KEMUDAHAN IMPOR TUJUAN EKSPOR PADA DIREKTORAT JENDERAL BEA DAN CUKAI - , LUKMAN HAKIM; , Prof. Gudono MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to evaluate the audit program guide of the recipient company of Ease Import for Export Destination (KITE) facilities. In the evaluation, the Regulations KITE used as criteria. Research on the Audit Report on the 11 recipient companies KITE facilities were also performed to obtain information relevant supporting audit procedures that the auditor had done, but not in the the audit program guide. In addition information was also gathered through discussions with 4 audit practitioners and 2 people involved in drafting the audit regulations to refine the results of the evaluation result. The results of the evaluation concluded that the audit program guide was required in the form of minimum standards. Audit program guide need added NIPER updating compliance testing procedures, testing procedures of the suitability of the realization subcontract with NIPER and testing the truth of export goods that serve as the accountability of completion of export. In addition it needs to be made an audit handbook which contains unique experience that experienced auditors in the audit.